High-throughput 96-well plate-based porcine antibody isolation protocol - John Byrne; Christina Bourne; Sitka Eguiluz; Stephanie N. Langel; Elisa Crisci (PLoS ONE, 2025)
For decades, scientists have used column chromatography to purify an array of analytes. The same chromatography system has also been deployed for the isolation and purification of antibodies to increase sensitivity and specificity of detection assays such as western blot, enzyme-linked immunosorbent assay (ELISA), and immunohistochemistry. However, even with the combination of these modalities the detection of specific antibodies developed in response to treatment, like vaccination, remains difficult due to physiological differences among species, sample types evaluated, and differing physiological states. Therefore, we developed a high-throughput antibody isolation protocol to measure influenza-specific antibodies in pregnant and lactating pigs, because the samples, in particular serum, milk and colostrum, contain components that cause high background. We developed a high-throughput 96-well plate-based method using a modified column chromatography technique to specifically isolate swine immunoglobulin (Ig) isotypes. This method utilizes isotype-specific reagents to isolate the IgG and IgA antibody isotypes from various fluids collected at multiple time points from individual animals following immunization. After sample processing and antibody isolation, the results showed a rapid and consistent yield of specific IgG and IgA, with comparable outcomes between single-column chromatography and our 96-well plate system, the latter offering a time-saving advantage. Specifically, the standard single-column chromatography required 2 to 3 hours to isolate 12 samples, whereas our method enabled the isolation of 192 samples in just 8 to 9 hours making this the ideal method for an immunogenicity study utilizing a variety of animal samples from multiple timepoints.